Job search methods, intensity and success in Britain in the 1990s - René Böheim; Mark P Taylor (Johannes Kepler University of Linz, Department of Economics, 2002)
We investigate the use of various job search strategies and their impact on the probability of subsequent employment and the re-employment wage among working age men in Britain. We find that replying to advertisements and using Job Centres are the two most common methods of job search and that job search intensity, and direct applications to employers in particular, result in a higher probability of subsequent employment. Conditional on finding work, replying to advertisements results in higher paying employment. Age, education, family circumstances and local labour demand emerge as key determinants of job search strategy use.
Keywords: J11; J20; J62; J64; C33; 330; job mobility; unemployment; BHPS; panel data; job search; Arbeitsplatzsuchmodell; Arbeitslosigkeit; Schätzung; Großbritannien